UPAYA ISLAM DALAM MEMBENDUNG BUDAYA KORUPSI - Syarif, Zainuddin (JURNAL KARSA (Terakreditasi No. 80/DIKTI/Kep/2012), 2012)
AbstractCorruption is one of chronic diseases in Indonesia. A country that has majority population of Islam has the highest population level. The causes are the bad character of state apparatus and the damage ofÂ Â Â Â Â  political system and government Thatâs why Islam offers some solutions to solve corruption, such as proper salary, avoiding to receive a bribe and present, the counting of treasure in the first and the last ofÂ  position period, a goodÂ  model leader, equitable punishment and the most thing isÂ  the controllingÂ Â Â  from society.Kata-kata kunciKorupsi, koruptor, Islam, Sayyidina Umar bin al-Khattab